2009
DOI: 10.1002/cncr.24204
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of liposomal cytarabine in lymphoma patients with central nervous system involvement from lymphoma

Abstract: BACKGROUND:Standard intrathecal chemotherapy for lymphomatous meningitis (LM) is limited by the short cerebrospinal half‐lives of the agents used, necessitating frequent administration. Liposomal cytarabine (DepoCyte) has an extended half‐life that permits administration at 2‐ to 4‐weekly intervals.METHODS:Patients with LM who underwent treatment with liposomal cytarabine at treatment centers in Spain between 2004 and 2007 were identified. Data on demographics, treatment, and outcomes were extracted from medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
2
19
0
1
Order By: Relevance
“…This is comparable to our results where 12 out of 51 patients (23.5%) developed leukopenia grade 3-4 and 80.4% of patients received a concomitant chemotherapy [11]. However, in several trials, there is a lack of information concerning hematological side effects [5,18]. The reported low incidence of nausea and vomiting in our study was in accordance with the reported incidence of several other prospective studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is comparable to our results where 12 out of 51 patients (23.5%) developed leukopenia grade 3-4 and 80.4% of patients received a concomitant chemotherapy [11]. However, in several trials, there is a lack of information concerning hematological side effects [5,18]. The reported low incidence of nausea and vomiting in our study was in accordance with the reported incidence of several other prospective studies.…”
Section: Discussionsupporting
confidence: 81%
“…It occurs most often in patients with advanced-stage breast cancer (up to 5% of patients), lung cancer (up to 11% of patients), and melanoma (up to 20% of patients) [2]. Regarding hematological malignancies, two multicenter trials in adults with newly diagnosed acute lymphoblastic leukemia showed an incidence of approximately 10% [3,][4], whereas the reported incidence of NM in patients with lymphomas ranges between 7 and 10% [5]. …”
Section: Introductionmentioning
confidence: 99%
“…103,104 The superiority of LC over conventional cytarabine in the treatment of lymphomatous meningitis has been demonstrated in a randomized clinical trial, 76 and several studies have shown significant efficacy of LC. [104][105][106] In terms of safety, LC should be administered with concurrent dexamethasone therapy, 107,108 maintaining an adequate interval between LC administration and that of other potential neurotoxic cytostatic drugs, especially intravenous HD-MTX and HD-cytarabine. 78,107 Intraventricular or IT administration of rituximab may be of value in the treatment of patients with recurrent CD20-positive CNSL.…”
Section: Intrathecal Therapymentioning
confidence: 99%
“…[3][4][5][6][7] Previously, the efficacy of liposomal cytarabine had been reported in individual cases or case series with mixed hematologic malignancies. Complete response rates ranged between 60% and 100% for adult and pediatric ALL, [15][16][17] various lymphomas, 18 human immunodeficiency virus-associated lymphoma, 19 acute myeloid leukemia 20 and chronic myeloid leukemia in myeloid blast crisis. 21 The populations of patients and the treatments were not very well defined in these retrospective case series.…”
Section: Patients Cyclesmentioning
confidence: 99%
“…In several studies, liposomal cytarabine was administered in combination with systemic therapy including high-dose cytarabine 20,26 or high-dose methotrexate. 18 With frequent administrations in combination with the hyper-CVAD regimen a number of severe neurotoxicities was observed 24 whereas liposomal cytarabine was well tolerated given less frequently 27 and not in combination with systemic high-dose cycles.…”
Section: Patients Cyclesmentioning
confidence: 99%